(untitled) (Revista da Faculdade de Odontologia - UPF, 2011)
Objective: This in vivo experimental study evaluated the effect of methotrexate on the oral mucosa of mice. Methodology: A total of 28 adult BALB/c mice were randomly assigned into a control and an experimental group. Mice in the experimental group were immunosuppressed with 2.5 mg/kg of methotrexate for three consecutive days. One mouse from each group was sacrificed each day for 10 days. Samples from ventral mucosal tongue surface were collected and prepared for histomorphometric analysis, by staining with hematoxylin/eosin. Three microscopic fields per section were analyzed, in order to evaluate the mean epithelial cells layer thickness and counting of blood vessels. To evaluate the existence of inflammatory infiltration, values of 0 and 1 were used for absence or presence, respectively. Results: The results showed that the treatment did not induce clinical signs of mucositis in the ventral mucosal tongue region. The histological examination showed that the mean number of blood vessels was similar in control and experimental samples (p < 0.001), and that there was absence of inflammatory infiltration. However, the thickness of the epithelial cell layer of experimental samples was significantly lower than in control samples. Conclusion: This study showed that, in the mouse model, methotrexate-induced mucositis histological result in manifestations in the ventral tongue region.